Parasitoid Diversity and Host-Parasitoid Interaction in Oil Palm Plantations with Different Management System - Muhammad Iqbal Tawakkal; Damayanti Buchori; Akhmad Rizali; Adha Sari; Pudjianto Pudjianto (Jurnal Perlindungan Tanaman Indonesia, 2019)
Parasitoids play an important role in controlling pests, including pests of oil palm. To maximize biological control technique using parasitoids, interactions between pests and parasitoids need to be studied. This research aimed to study parasitoid diversity and host-parasitoid interaction in oil palm plantation with the different management system. The field research was conducted in oil palm plantation own by smallholder and company (PT Humusindo) in Jambi. Sampling insects was conducted by collecting pests (parasitoid host) on oil palm trees with age of four years old. Eggs, larvae, and pupae of the pests were taken directly by hand then reared in the laboratory to know their parasitoids. Pests and parasitoids emerged were identified up to morphospecies or species level. A total of 176 lepidopteran pests consisting of 15 morphospecies and 6 families, and 650 parasitoids consisting of 21 morphospecies and 12 families have been collected. Nine morphospecies of pests from 25 individuals were found in smallholder plantation and 14 morphospecies of pests from 151 individuals in company plantation. Eight morphospecies of 26 parasitoids were found in smallholder plantations and 8 morphospecies of 624 parasitoids in the company plantation. The interaction structure between pests and parasitoids is more complex in the company plantation than in smallholder plantations. Family Braconidae and Ichneumonidae are the most parasitoids found and associated with nettle caterpillars. The different of the management system of oil palm plantation did not affect the diversity and abundance of pests as well as their parasitoids in oil palm plantations.